Vitamin D repletion ameliorates adipose tissue browning and muscle wasting in infantile nephropathic cystinosis‐associated cachexia. Issue 1 (13th November 2019) - Cheung, Wai W.; Hao, Sheng; Wang, Zhen; Ding, Wei; Zheng, Ronghao; Gonzalez, Alex; Zhan, Jian‐Ying; Zhou, Ping; Li, Shiping; Esparza, Mary C.; Hoffman, Hal M.; Lieber, Richard L.; et al.
Abstract: Background: Ctns −/− mice, a mouse model of infantile nephropathic cystinosis, exhibit hypermetabolism with adipose tissue browning and profound muscle wasting. Ctns −/− mice are 25(OH)D3 and 1, 25(OH)2 D3 insufficient. We investigated whether vitamin D repletion could ameliorate adipose tissue browning and muscle wasting in Ctns −/− mice. Methods: Twelve‐month‐old Ctns −/− mice and wild‐type controls were treated with 25(OH)D3 and 1, 25(OH)2 D3 (75 μg/kg/day and 60 ng/kg/day, respectively) or an ethylene glycol vehicle for 6 weeks. Serum chemistry and parameters of energy homeostasis were measured. We quantitated total fat mass and studied expression of molecules regulating adipose tissue browning, energy metabolism, and inflammation. We measured lean mass content, skeletal muscle fibre size, in vivo muscle function (grip strength and rotarod activity), and expression of molecules regulating muscle metabolism. We also analysed the transcriptome of skeletal muscle in Ctns −/− mice using RNAseq. Results: Supplementation of 25(OH)D3 and 1, 25(OH)2 D3 normalized serum concentration of 25(OH)D3 and 1, 25(OH)2 D3 in Ctns −/− mice, respectively. Repletion of vitamin D partially or fully normalized food intake, weight gain, gain of fat, and lean mass, improved energy homeostasis, and attenuated perturbations of uncoupling proteins and adenosine triphosphate content in adipose tissue and muscle in Ctns −/− mice. Vitamin D repletion attenuated elevated expression of beige adipose cell biomarkers (UCP‐1, CD137, Tmem26, and Tbx1) as well as aberrant expression of molecules implicated in adipose tissue browning (Cox2, Pgf2α, and NF‐κB pathway) in inguinal white adipose tissue in Ctns −/− mice. Vitamin D repletion normalized skeletal muscle fibre size and improved in vivo muscle function in Ctns −/− mice. This was accompanied by correcting the increased muscle catabolic signalling (increased protein contents of IL‐1β, IL‐6, and TNF‐α as well as an increased gene expression of Murf‐2, atrogin‐1, and myostatin) and promoting the decreased muscle regeneration and myogenesis process (decreased gene expression of Igf1, Pax7, and MyoD) in skeletal muscles of Ctns −/− mice. Muscle RNAseq analysis revealed aberrant gene expression profiles associated with reduced muscle and neuron regeneration, increased energy metabolism, and fibrosis in Ctns −/− mice. Importantly, repletion of 25(OH)D3 and 1, 25(OH)2 D3 normalized the top 20 differentially expressed genes in Ctns −/− mice. Conclusions: We report the novel findings that correction of 25(OH)D3 and 1, 25(OH)2 D3 insufficiency reverses cachexia and may improve quality of life by restoring muscle function in an animal model of infantile nephropathic cystinosis. Mechanistically, vitamin D repletion attenuates adipose tissue browning and muscle wasting in Ctns −/− mice via multiple cellular and molecular mechanisms.